Trematode fauna of fish inhabiting reservoirs of the European part of Russia - N. N. Romanova; N. A. Golovina; A. A. Vishtorskaya; P. P. Golovin (Российский паразитологический журнал, 2023)
The purpose of the research is an ecological and faunal analysis of trematodes in fish inhabiting reservoirs of the European part of Russia.Materials and methods. Helminthological studies were conducted in 23 reservoirs of the European part of Russia from 2011 to 2021. The fish aged two to seven years were analyzed by methods generally accepted in ichthyoparasitology.Results and discussion. Twelve fish species from families Cyprinidae, Percidae, Esocidae and Odontobutidae were found to be infected with 29 trematode species from 14 genera which were represented by 68.9% of metacercariae. Most trematodes had a wide specificity: Tylodelphys clavata was found in 9 fish species; Diplostomum spathaceum and Paracoenogonimus ovatus in 7 species and Apophallus muehlingi in 6 species. The expanded host range for T. podicipina was observed. A. muehlingi, which is an alien species for the Volga-Caspian fisheries basin was identified in most reservoirs. Trematodes by their prevalence in reservoirs are divided into background (5 species), common (6), rare (8) and very rare (10) trematodes. Trematode fauna of fish in reservoirs included 6 to 16 species. The highest species diversity was detected in the Belgorod (16 species), Yakhroma (13 species), Uglich and Chelnav (12 species), Pestovsk and Pyalovsk (11 species) reservoirs. Fifteen trematode species were found in the perch; 12, in the bream and roach; 9, in the pike perch; 8, in the pike and rudd; 6, in the ruff and white bream; 4, in the Volga pikeperch and crucian carp; 3, in the tench; and 1, in the Amur sleeper. The formed foci of trematode infections were observed, namely, postodiplostomosis and ichthyocotylurosis infection. Three trematode species, Pseudoamphistomum truncatum, A. muehlingi and Rossicotrema donicum, were detected that pose a real and potential danger to human health and warm-blooded animals.